Effect of infrared laser surface treatment on the microstructure and properties of adhesively CFRP bonded joints. (October 2018) - Zhan, Xiaohong; Li, Yun; Gao, Chuanyun; Wang, Hongen; Yang, Yang
Highlights: The infrared laser leads to the characteristic thermal expansion. The infrared laser causes the carbon fibers to be burned. The infrared laser surface processing is performed prior to adhesive bonding. The bonding strength of the joints treated by infrared laser is low. Abstract: Adhesive bonding is considered to offer advantages over the connections of the aircraft composite structures. The infrared laser surface processing of various laser process parameters and peel ply treatment are performed in this study. To investigate the microstructure and properties of adhesively bonded composite single-lap joints obtained by infrared laser surface treatment and peel ply processing, the examinations of microstructures, surface free energy and shear strength of the joints are conducted. The results indicate that the adhesively bonded joints acquired by infrared laser treatment have lower average shear strength of 20.158 MPa, comparing with the joints of 32.574 MPa in average shear strength treated by peel ply processing. In addition, the surface roughness test is conducted and the surface roughness of 4.926 μm of the specimen after peel ply treatment is higher than that of the specimen after infrared laser treatment.